2021
DOI: 10.3390/ijms22126366
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Role of HSF1 in Pathophysiology: Focus on Its Interplay with TG2

Abstract: The cellular environment needs to be strongly regulated and the maintenance of protein homeostasis is crucial for cell function and survival. HSF1 is the main regulator of the heat shock response (HSR), the master pathway required to maintain proteostasis, as involved in the expression of the heat shock proteins (HSPs). HSF1 plays numerous physiological functions; however, the main role concerns the modulation of HSPs synthesis in response to stress. Alterations in HSF1 function impact protein homeostasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 166 publications
(197 reference statements)
2
7
0
Order By: Relevance
“…By contrast, when cells are injured and the intracellular Ca 2+ concentration increases, it acts as a crosslinking, playing a key role in autophagy, or PDI enzyme and if the cellular damage is irreversible inducing cell death [ 13 , 56 , 62 ]. In keeping with these findings TG2 has been shown to be involved in the pathogenesis of the major human diseases [ 50 , 52 , 75 ]. Another TG2 feature is its intracellular distribution, in fact, although it is predominantly found in cytoplasm it is also distributed in various subcellular locations including plasma membrane, mitochondria and nucleus [ 2 , 4 , 57 ].…”
Section: Transglutaminase Typesupporting
confidence: 60%
See 2 more Smart Citations
“…By contrast, when cells are injured and the intracellular Ca 2+ concentration increases, it acts as a crosslinking, playing a key role in autophagy, or PDI enzyme and if the cellular damage is irreversible inducing cell death [ 13 , 56 , 62 ]. In keeping with these findings TG2 has been shown to be involved in the pathogenesis of the major human diseases [ 50 , 52 , 75 ]. Another TG2 feature is its intracellular distribution, in fact, although it is predominantly found in cytoplasm it is also distributed in various subcellular locations including plasma membrane, mitochondria and nucleus [ 2 , 4 , 57 ].…”
Section: Transglutaminase Typesupporting
confidence: 60%
“…This potential kinase activity is able to phosphorylation the p53 tumor suppressor protein [ 46 ], histones H1–4 [ 47 ] and retinoblastoma (Rb) protein [ 45 ]. More recently due to the improvement of the omics approaches an important function of TG2 as scaffold protein has been reported under different physio/pathological settings [ 26 , 50 , 52 , 71 , 73 ]. The 3D structure of TG2 is composed of four domains: an NH2-terminal β-sandwich domain; a catalytic core domain containing a catalytic triad for the acyl-transfer reaction (Cys277, His335 and Asp358); a β-barrel1 domain, containing GDP/GTP-interacting residues, that is involved in receptor signalling and a β-barrel2 domain [ 25 ].…”
Section: Transglutaminase Typementioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that doxorubicin promotes TG2 and IRF3 nuclear translocation paralleled by the nuclear IRF3 dimers formation, thus suggesting a correlation between these two events. It has been demonstrated that TG2 catalyzes the covalent cross-linking of several nuclear proteins including various transcription factors [ 19 , 20 ]. Thus, we evaluated whether TG2 could interact with IRF3 dimers.…”
Section: Resultsmentioning
confidence: 99%
“…HSPs are primarily induced in response to heat shock but can also be produced in response to a variety of environmental and cellular stresses, as well as diseases, such as neurodegenerative disorders and cancer [ 8 ]. HSPs are known to have cytoprotective effects, acting as molecular chaperones that help to refold or stabilize the unfolded proteins, to dissociate the toxic protein aggregates and to drive the misfolded proteins to degradation, thus contributing to organismal physiology and pathophysiology [ 9 ]. Therefore, there is a rising interest in deciphering the molecular mechanisms of HSF1 regulation, the interplay between the downstream signaling pathways and its broad role in proteostasis maintenance and thermotolerance.…”
Section: Introductionmentioning
confidence: 99%